2023
DOI: 10.3390/foods12071411
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Functional and Rheological Properties of Alternative Plant-Based Flours

Abstract: The use of alternative vegetal sources is a proposed strategy to improve the diversity and quality of plant-based products on the market, currently led by soy and pea. This study compares the techno-functional properties of seven vegetable flours (chickpea, lentil, red lentil, white bean, quinoa, amaranth, and oat) and the rheological properties of their flour pastes and gels. All techno-functional properties significantly (α = 0.05) varied depending on the type of flour. Among the flours studied, the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Chickpea gels form soft and less gummy gels that are less resistant to cutting but are stiffer than lentil gels. These differences seem to be attributed to different compositions of flours determined in a previous paper [18]. Lentil and red lentil gels with high protein content (25.9% and 24.0%, respectively) were harder, gummier, and more resistant than chickpea gels (16.9% protein).…”
Section: Figurementioning
confidence: 75%
See 1 more Smart Citation
“…Chickpea gels form soft and less gummy gels that are less resistant to cutting but are stiffer than lentil gels. These differences seem to be attributed to different compositions of flours determined in a previous paper [18]. Lentil and red lentil gels with high protein content (25.9% and 24.0%, respectively) were harder, gummier, and more resistant than chickpea gels (16.9% protein).…”
Section: Figurementioning
confidence: 75%
“…From a technological viewpoint, some pulse flours such as lentil, red lentil, and chickpea can also form strong gels that can be the basis of solid products [18][19][20][21][22]. Gels are mainly based on the formation of a three-dimensional network of a starch-protein matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins and polysaccharides may be responsible for the FS of taro flour. These compounds are good emulsifiers that may reduce surface tension and prevent coalescence (Arıcı et al, 2021;Badia-Olmos et al, 2023). The solubility, structure, and amino acid composition of proteins present in flour greatly influence its FS, whereas proteins that are more hydrophobic and less soluble at neutral pH may result in poor FS (Badia-Olmos et al, 2023).…”
Section: Foaming Stability (Fs)mentioning
confidence: 99%
“…These compounds are good emulsifiers that may reduce surface tension and prevent coalescence (Arıcı et al, 2021;Badia-Olmos et al, 2023). The solubility, structure, and amino acid composition of proteins present in flour greatly influence its FS, whereas proteins that are more hydrophobic and less soluble at neutral pH may result in poor FS (Badia-Olmos et al, 2023). With high FS, Moi and Kauaʻi Lehua varieties had higher protein content than the other varieties (Tables 1 and 3).…”
Section: Foaming Stability (Fs)mentioning
confidence: 99%
“…(Dhondiram et al, 2023 andSharma et al 2023) reported quinoa flour to be high in protein, fat, and ash. (Badia-Olmos et al 2023) reported 8.7% fiber in quinoa flour. Also, quinoa flour has high amounts of minerals, especially iron (8.42 mg/100 g), (Coţovanu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%